Eupatorium fortunei and Its Components Increase Antiviral Immune Responses against RNA Viruses - Choi, Jang-Gi; Lee, Heeeun; Hwang, Youn-Hwan; Lee, Jong-Soo; Cho, Won-Kyung; Ma, Jin Yeul (Frontiers in Pharmacology, 2017)
Eupatorium fortunei (EF) has long been used as herbal medicine in Korea, China, and Asian countries to treat a variety of diseases. Recent studies have reported that EF has anti-metastatic, anti-angiogenic, anti-bacterial, and anti-oxidant activities, as well as activities against malignant metastatic human cancers. The effect of EF and its components on viruses has not been reported. In the present study, the antiviral activity and mechanism of action of an aqueous extract of EF (WEF) and its components were evaluated in vitro. We found that pretreatment with WEF markedly reduced viral replication, as evaluated using a green fluorescent protein (GFP)-tagged virus (influenza A virus, Newcastle disease virus, and vesicular stomatitis virus) in murine RAW 264.7 macrophage cells. We demonstrated that WEF induces the production of type I IFN including pro-inflammatory cytokines. Additionally, we identified the active anti-viral components of WEF as quercetin, psoralen, and quercitrin. Thus, WEF and its active components are immunomodulators of the innate immune response in murine macrophages, a finding that is potentially useful to developing prophylactic or therapeutic treatments against a range of viruses.